The interplay between climate change and disaster risk reduction policy: evidence from Mexico. (3rd July 2017) - Ruiz-Rivera, Naxhelli; Lucatello, Simone
ABSTRACT: Mexico gained worldwide reputation for its efforts to develop both climate change (CC) and disaster risk reduction (DRR) policies at the national and international levels. However, the integration of agreements such as the Kyoto Protocol and the Hyogo and Sendai Frameworks into the national institutional setting has been challenging in terms of creating a coherent national risk reduction policy. The purpose of this paper is to analyse the interplay between DRR and CC domains; it provides evidence for the situation in Mexico by comparing the institutions and main actors in both fields as well as the financial and operational instruments currently in force. The comparison is based on institutions' jurisdictions, priorities and lines of action. This paper synthesises the most important policy instruments, their meeting points and their contradictions and discusses the implications of such policy setting for the implementation of effective CC risk policies. The study depicts a fragmented policy interface with serious shortcomings in terms of the institutional design necessary to coordinate actions. The article concludes that, despite the multiple conceptual and political intersections between both policy fields, the implementation of specific, shared actions would hardly overcome the difficulties imposed by the current, fragmented normative frameworks and jurisdictions.